Potrait of Physical Condition of Extracurricular Sports Students SMPN 1 Pakis - Cahyana Putra, Heru Hardiansyah; Winarno, Mashuri Eko; Alfani, Muhammad Aliffajaruddin; Aji, Galih Purnomo (Fakultas Ilmu Keolahragaan Universitas Negeri Malang, 2024)
In order to support daily activities, every individual must have good physical fitness. In addition, physical activity has an important role in the well-being and health of students considering the physical, mental and social benefits. The purpose of this research is to analyze the level of physical condition of students who take part in extracurricular sports. The method used is descriptive with a survey approach. The population in this research are students who take part in extracurricular volleyball, basketball, and pencak silat with a total of 66 students. The test instrument used the Indonesian physical fitness test (TKJI) 13-15 years. The test components include 50-meter sprint, 60-second body lift, 60-second sit-up, upright jump and 1000-meter long distance run. The results showed that male students obtained a score with a percentage of 46% with a physical fitness category of less than once. For female extracurricular participants with obtained a score of results with a percentage of 38% with a physical fitness category of less than once. The conclusion of the research is that the average results of the physical condition of students who take part in extracurricular sports are in the very poor category, so this is a task for coaches to develop a good and appropriate program to improve the level of physical condition of extracurricular participants.